FASILITAS PENDIDIKAN KEJURUAN ANIMASI DI JAKARTA PUSAT MELALUI PROGRAM PENDIDIKAN 5.0 - Mentari Amaliah Susanto; Rudy Surya (Jurusan Arsitektur dan Perencanaan, 2022)
Animation technology until now has always experienced rapid development, especially in developed countries that have technology that is considered very advanced and qualified with the quality of its human resources. Currently the animation industry in developed countries continues to progress in creating extraordinary animation works so that the whole world can experience their works, including in Indonesia. Indonesia also has its own animation industry, although in terms of quality it is not comparable to developed countries such as in America and Europe, but animation in Indonesia is currently experiencing development. In Indonesia, animation education tends to be lacking, therefore the current government wants to develop and advance the animation education sector, which is currently dominated by foreign animation on Indonesian television. For this reason, animation education facilities are needed to hone and create a young generation who has superior quality in the field of animation. This animation vocational education facility project aims to develop and hone the younger generation to achieve their goals in the industry, which is currently still relatively small by opening an educational facility that focuses on the field of animation. In designing this animation education facility project, the school's architectural typology design method was applied as a basis based on function, especially in producing the organization of space and building form in order to be able to answer rethinking about the typology of school buildings, especially Animation Vocational Education in Jakarta. In addition, it also applies the Eco Industrial design method to building design. Keywords: animation industry; technology; school typology AbstrakTeknologi animasi hingga saat ini selalu mengalami perkembangan yang pesat, terutama di negara-negara maju yang memiliki teknologi yang terbilang sangat maju dan mumpuni dengan kualitas sumber daya manusia-Nya. Saat ini industri animasi di negara maju terus mengalami kemajuan dalam menciptakan karya animasi yang luar biasa hingga seluruh dunia dapat merasakan karya-nya, termasuk di Indonesia. Indonesia juga memiliki industri animasi tersendiri, walaupun dari segi kualitas belum sebanding dengan negara maju seperti pada negara Amerika dan Eropa, namun animasi di Indonesia saat ini mengalami perkembangan. Di Indonesia, dalam pendidikan animasi cenderung kurang, maka dari itu pemerintah saat ini ingin mengembangkan dan memajukan sektor pendidikan animasi yang saat ini di pertelevisian Indonesia didominasi oleh animasi luar. Untuk itu diperlukan sarana pendidikan animasi untuk mengasah dan menciptakan generasi muda yang memiliki kualitas unggul dalam bidang ilmu animasi. Proyek sarana pendidikan kejuruan animasi ini bertujuan untuk mengembangkan dan mengasah para generasi muda untuk menggapai cita-cita dalam industri tersebut, yang saat ini masih terbilang sedikit dengan membuka suatu fasilitas pendidikan yang berfokus pada bidang animasi. Dalam mendesain proyek sarana pendidikan animasi ini menerapkan metode desain tipologi arsitektur sekolah sebagai dasar berdasarkan fungsi, khususnya dalam menghasilkan organisasi ruang dan bentuk bangunan agar dapat menjawab berpikir ulang tentang tipologi bangunan sekolah khususnya Pendidikan Kejuruan Animasi di Jakarta. Selain itu juga menerapkan pada metode desain Eco Industrial pada desain bangunan.